Heterogeneity and the welfare cost of dynamic factor taxes - Zsolt Becsi (Federal Reserve Bank of Atlanta, 1999)
The welfare costs of dynamic factor taxes are analyzed in a dynamic general equilibrium model with heterogeneous endowments, abilities, and tastes. Conventional functional form restrictions yield formulas for the transition effects and marginal welfare costs of factor taxes. Heterogeneity implies that taxes have feedback or distribution effects, beyond standard efficiency effects, that may lead to nonstandard aggregate dynamics. Also, marginal welfare costs vary systematically with initial distortions and agents' characteristics. Because factor taxes lower wealth inequality, equity gains offset efficiency losses with the offset weakening as initial distortions rise. However, distribution effects reinforce efficiency losses unless preexisting distortions are sufficiently high, in which case some types of heterogeneity yield offsetting distribution effects. Simulations suggest that, for labor taxes, distribution effects dominate dynamics, but not for capital taxes. Also, equity gains dominate efficiency losses and distribution effects for the marginal welfare cost of labor taxes, and vice versa for capital taxes.
Keywords: 330; Welfare; Taxation